2020
DOI: 10.1002/chem.201904600
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Systematic Structural Analysis of Cationic Half‐Sandwich Ruthenium Chalcogenocarbonyl Complexes

Abstract: Although the chemistry of transition‐metal complexes with carbonyl (CO) and thiocarbonyl (CS) ligands has been well developed, their heavier analogues, namely selenocarbonyl (CSe) and tellurocarbonyl (CTe) complexes remain scarce. The limited availability of such CSe and CTe complexes has so far hampered our understanding of the differences between such chalcogenocarbonyl (CE: E=O, S, Se, Te) ligands. Herein, we report the synthesis and properties of a series of cationic half‐sandwich ruthenium CE complexes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
(77 reference statements)
3
3
0
Order By: Relevance
“…Accordingly, for transition metal chalcocarbonyl complexes, L n MCE, the MC bond becomes stronger and the CE bond weaker upon descending group 16 . In valence bond terms (Figure ) one may consider canonical forms ( ii ) and ( iii ) as providing only a minor contribution to the resonance description of CO complexes, but an increasingly substantial contribution to the overall bonding of CS, CSe and CTe complexes . This also results in an increasingly strong trans influence in the order CO<CS<CSe<CTe.…”
Section: Structure and Bondingsupporting
confidence: 72%
See 3 more Smart Citations
“…Accordingly, for transition metal chalcocarbonyl complexes, L n MCE, the MC bond becomes stronger and the CE bond weaker upon descending group 16 . In valence bond terms (Figure ) one may consider canonical forms ( ii ) and ( iii ) as providing only a minor contribution to the resonance description of CO complexes, but an increasingly substantial contribution to the overall bonding of CS, CSe and CTe complexes . This also results in an increasingly strong trans influence in the order CO<CS<CSe<CTe.…”
Section: Structure and Bondingsupporting
confidence: 72%
“…Similar conclusions emerged more recently from highly detailed systematic studies which examined three sets of ruthenium chalcocarbonyls; [RuCl 2 (CE)(H 2 IMes)(DMAP) 2 ] ( 2‐E ), [RuCl(CE)(H 2 IMes)(η 5 ‐C 5 H 5 )] ( 3‐E ) and [Ru(CE)(CNCH 2 Ts)(H 2 IMes)(η 5 ‐C 5 H 5 )][BAr F 4 ]( 4‐E ) (H 2 IMes=1,3‐dimesitylimidazolin‐2‐ylidene; DMAP=4‐(dimethylamino)pyridine; Ts= p ‐toluenesulfonyl; Ar F =C 6 H 3 (CF 3 ) 2 –3,5, Figure ). The experimental results from these studies confirmed that, upon descending group 16, trans ligand dissociation rates increased and the M–CE distances shorten as π‐acidity of the CE ligands increases.…”
Section: Structure and Bondingsupporting
confidence: 58%
See 2 more Smart Citations
“…Two mechanisms to make the π* orbitals the LUMOs have been demonstrated in extant examples: (i) substituents with extended π systems that can accommodate additional electrons ,,,,, or (ii) additional ligands that force a change in coordination number and drive metal orbital energies below those of ligand LUMOs and facilitate ligand reduction. , Herein, we report a third and potentially more general approach. When the donor atoms are S, and not O or N, the π* orbitals are lower in energy and sufficiently so as to accept electrons, as we have now observed in the {Pt­(cta) 2 } system.…”
Section: Discussionmentioning
confidence: 99%